MediaPro 2.5. - Smith, Lee Anne (Architectural Record, 2004)
This article presents information on MediaPro 2.5, a program for browsing, organizing, presenting, and cataloging large image and animation libraries. Once available only for Macs, the new Windows-compatible version has made it a more feasible option for design firms. The software is capable of handling 130 different file formats, including JPEGs, Photoshop documents, EPS files, QuickTime videos, and others. Files may be imported into MediaPro catalogs through a simple drag-and-drop technique.